H HIGH-FIDELITY SIMULATION DAN DEBRIEFING SEBAGAI MODEL PENINGKATAN INTERPROFESSIONAL COLLABORATION DALAM PENDIDIKAN KEPERAWATAN - Hery (LPPM Universitas Sari Mulia, 2020)
Background: In recent years high-fidelity simulation training using patient simulations has taken a large role in nursing education, in terms of interprofession involving collaboration of nurses and doctors. Objective: Analyzing the effectiveness of using debriefing techniques with high-fidelity simulation to improve interprofessional collaboration competencies in nursing education. Methods: Literature review from various ProQuest online journal databases, EBSCOhost, then grouped according to the theme and has been analyzed regarding the advantages and disadvantages of high-fidelity simulation Results: It was found that most studies have deficiencies and rigidity in high-fidelity simulation. However, it can be more effective if it is collaborated with the Debriefing method.